Recurrent Neuroendocrine Primary Cutaneous Mucinous Carcinoma of the Scalp After Complete Excision. (19th February 2023) - Levett, Kaitlyn; Taylor, Brandon; Krishnan, Bhuvaneswari; Ramani, Nisha S.
Abstract: Primary cutaneous mucinous carcinoma is a rare, indolent malignancy with a debated history regarding cell of origin. Recurrence is rare but has been documented in up to a third of cases. Recent literature reviews have recognized 2 possible subtypes—neuroendocrine and nonneuroendocrine— with different possible prognostic implications for patients. We describe a case of recurrent primary cutaneous mucinous carcinoma in a 50-year-old man with subtle neuroendocrine features not initially recognized on routine H&E staining but highlighted by immunohistochemical studies. We underscore the importance of immunohistochemical use in these rare cases and emphasize that awareness of these neuroendocrine and nonneuroendocrine subtypes is essential for a complete diagnosis.